2022
DOI: 10.3390/medicina58020194
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Implications and Effect of Supplementation in Endocrine Disorders: Autoimmune Thyroid Disorders (Hashimoto’s Disease and Grave’s Disease), Diabetes Mellitus and Obesity

Abstract: Background and Objectives: Vitamin D deficiency is involved in numerous pathologies, including endocrine pathology. The purpose of this review consists of presenting the role of vitamin D in the pathophysiology of certain endocrine disorders, autoimmune thyroid disorders (Hashimoto’s disease and Grave’s disease), diabetes mellitus, and obesity, and whether its supplementation can influence the outcome of these diseases. Materials and Methods: Review articles and original articles from the literature were consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 70 publications
2
10
1
Order By: Relevance
“…The present study suggests an inverse relationship between vitamin D levels and TSH in children with non-autoimmune hypothyroidism. This aligns with evidence demonstrating vitamin D supplementation's impact on TSH in autoimmune thyroid disease (18,19). Galusca et al's meta-analysis exempli es this, decreased TSH and thyroid antibodies upon supplementation (19).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The present study suggests an inverse relationship between vitamin D levels and TSH in children with non-autoimmune hypothyroidism. This aligns with evidence demonstrating vitamin D supplementation's impact on TSH in autoimmune thyroid disease (18,19). Galusca et al's meta-analysis exempli es this, decreased TSH and thyroid antibodies upon supplementation (19).…”
Section: Discussionsupporting
confidence: 77%
“…This aligns with evidence demonstrating vitamin D supplementation's impact on TSH in autoimmune thyroid disease (18,19). Galusca et al's meta-analysis exempli es this, decreased TSH and thyroid antibodies upon supplementation (19). Similarly, Metwalley et al's study in children with autoimmune hypothyroidism yielded comparable results (18).…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, Vitamin D is connected to numerous CVDs, including infectious myocarditis, which is caused by aberrant immunological reactions as a result of vitamin D receptor inadequacy. 38,39 In the current study, we found that people with prediabetes have greater CVR scores than normal participants regardless of their (25(OH)D) levels, we also did not identify a significant link between HbA1c and (25(OH)D) levels in prediabetics or healthy participants.…”
contrasting
confidence: 72%
“…The serum concentration of vitamin D showed a significantly lower value in Graves’ disease patients who were not in remission compared to those who were. Moreover, in a randomized prospective study, the thyroid volume and the degree of exophthalmos revealed a statistically significant correlation with vitamin D levels [ 105 , 106 ].…”
Section: Vitamin D Deficiency and Epigenetic Dysregulations In Autoim...mentioning
confidence: 99%